2014
DOI: 10.1007/s13313-014-0328-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different chemical and biological products in the control of Pseudomonas syringae pv. actinidiae on kiwifruit

Abstract: The recent outbreak of bacterial canker on kiwifruit, caused by Pseudomonas syringae pv. actinidiae, has caused considerable damage to the international kiwifruit industry. Commercial products, and products under development, were evaluated over 2 years to assess their ability to control bacterial canker on kiwifruit under controlled conditions. The results were compared with two trials carried out in a kiwifruit orchard located in northern Italy during 2011 and 2012, to test the preventative efficacy of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
(22 reference statements)
1
28
0
1
Order By: Relevance
“…However, with some plant, defence elicitors such as ASM (Reglinski et al, ) and commercial microbial biopesticides based on Bacillus spp. against Psa (Monchiero, Gullino, Pugliese, Spadaro, & Garibaldi, ), a lack of consistency in efficacy has been demonstrated under some limited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, with some plant, defence elicitors such as ASM (Reglinski et al, ) and commercial microbial biopesticides based on Bacillus spp. against Psa (Monchiero, Gullino, Pugliese, Spadaro, & Garibaldi, ), a lack of consistency in efficacy has been demonstrated under some limited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several bacterial isolates present as epiphytes in kiwifruit orchards were confirmed to be copper resistant or copper tolerant [30]: among them, at least two isolates, collected in kiwifruit orchards, have been demonstrated to be copper resistant and their ability to transfer such resistance to Psa has been studied [30]. The choice of a prospective antagonist to be used as biocontrol agent for the inhibition of the inoculum build up on plant organs, especially on leaves, should be done by carefully testing and confirming its susceptibility to low (<30 ppm) copper treatment rates, since the concentration of Cu ++ sprayed in kiwifruit orchards during the chemical control of the bacterial canker implies the use of copper bactericides at a concentration starting from 30-50 ppm [37,38]. Altimira et al [39] reported the presence of copper resistant bacteria and bacterial communities in agricultural soils with the presence of high copper pollutants, and kiwifruit orchards are notoriously sprayed with copper compounds several times a year, to control both phytopathogenic bacteria and some fungi [38,40].…”
Section: Copper Tolerancementioning
confidence: 99%
“…The choice of a prospective antagonist to be used as biocontrol agent for the inhibition of the inoculum build up on plant organs, especially on leaves, should be done by carefully testing and confirming its susceptibility to low (<30 ppm) copper treatment rates, since the concentration of Cu ++ sprayed in kiwifruit orchards during the chemical control of the bacterial canker implies the use of copper bactericides at a concentration starting from 30-50 ppm [37,38]. Altimira et al [39] reported the presence of copper resistant bacteria and bacterial communities in agricultural soils with the presence of high copper pollutants, and kiwifruit orchards are notoriously sprayed with copper compounds several times a year, to control both phytopathogenic bacteria and some fungi [38,40]. Therefore, the possibility of detecting copper resistance endophytes should not be excluded.…”
Section: Copper Tolerancementioning
confidence: 99%
“…Psa started to infects severely Actinidia chinensis on orchards cultivated in Central Italy and since 2009 new outbreaks have affected orchards of both A. deliciosa (cv Hayward) and A. chinensis in the main kiwifruit producing areas of Italy (Armentano 2010). To date, the bacterial disease is limiting the possibility of cultivating kiwifruit, in particular in the areas of northern Italy, where the climate pattern, creates favourable conditions for the pathogen spread (Monchiero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Psa is, at the moment the major source of losses in kiwifruit production because it is responsible for both economic losses in fruit production and plant mortality in the orchards (Monchiero et al, 2015). For these reasons, researchers and kiwifruit industry have done considerable works and progresses in understanding Psa.…”
Section: Introductionmentioning
confidence: 99%